ECOLINGUISTIC PERSPECTIVES ON EFL LEARNERS’ CULTURAL IDENTITY POST SUMATRA FLOODS - Nurul Inayah Hutasuhut; Rizki Ananda; Rani Rakasiwi (Ensiklopedia of Journal, 2025)
Abstract: This study analyzes the perception and storytelling of the changes in cultural identity of English as a Foreign Language (EFL) learners in Aceh and Padang after the 2025 Sumatra floods - landslides from an ecolinguistics perspective. Adopting an explanatory mixed-methods design and a retrospective perceived change framework, survey data from 800 senior high school and university students and qualitative data of 60 participants were acquired through narrative and interview data rendering this study to be explanatory and qualitative. Quantitative findings show perceived moves towards more layered configurations of cultural identity where both strongly local and national affiliations are observed along with enhanced functional orientation towards global culture and towards English. In addition, learners report decreases in debilitating cultural anxiety, approaching what Anxiety/Uncertainty Management theory describes as optimal levels of uncertainty. Qualitative ecolinguistic analysis shows that negotiation of identity occurs at macro, meso, exo and micro ecological levels mediated by religious and cultural discourses, family and school practices, institutional responses, media representations and multilingual language use. Rather than a linear movement from local to global identity, learners create hybrid, non-zero-sum narratives of identity that strategically mobilize local languages, Indonesian and English in post-disaster contexts. The study contributes to the field of ecolinguistics and applied linguistics by showing how environmental catastrophe may catalyze reflexive identity negotiation among EFL learners in disaster-prone regions of the Global South countries and how the study highlights the implications for disaster-responsive and identity-sensitive English language education.Keywords: EFL, Cultural Identity, Ecolinguistics, Sumatra, Floods-landslides